Peningkatan Pengetahuan Anggota Kelompok Tani Mitra Tani Desa Paranda Kecamatan Wula Waijelu Dalam Pembuatan Pestisida Organik Berbasis Kearifan Lokal - Killa, Yonce Melyanus; Ndapamuri, Melycorianda Hubi; Jawang, Uska Peku; Nganji, Marten Umbu; Lewu, Lusia Danga; Kapoe, Suryani KKL; Duang, Antonius Ndana; Kita, Yakobus (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The Mitra Tani Farmer Group is a farmer group in Paranda Village, Wula Waijelu District, East Sumba Regency. Agricultural activities carried out often have problems with plant pests (OPT). The existence of problems regarding OPT can be controlled by using pesticides, one of which is vegetable pesticides. The results of the community service activities showed that the members of the Mitra Tani farmer group finally learned about some local ingredients that could be used as organic pesticides. Local materials that can be used as organic pesticides include gamal leaves, tai kabala leaves (kirinyuh/ Chromolaena odorata L.), anona leaves, neem leaves, papaya leaves, yam iwi (gadung tuber), and soursop leaves. The members are also active in community service and learning activities and play an active role in making organic pesticides.